1995
DOI: 10.1063/1.115224
|View full text |Cite
|
Sign up to set email alerts
|

Delayed photocurrent affected by Γ-X resonance in GaAs/AlAs type-I short-period superlattices

Abstract: Observation of the type I-type II crossover in GaAs/AlAs shortperiod superlattices by optical spin orientation J. Appl. Phys. 69, 2532 (1991); 10.1063/1.348693Study of the directindirect bandgap transition in GaAs/AlAs shortperiod superlattices using photocurrent spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recently, it was demonstrated that ⌫-X transport can drastically influence the carrier transport in type-I SL's. 4,5 In weakly coupled, type-I SL's, resonant tunneling in the conduction band usually occurs between different ⌫ subbands. For small carrier densities, the electric-field distribution across the superlattice is homogeneous.…”
mentioning
confidence: 99%
“…Recently, it was demonstrated that ⌫-X transport can drastically influence the carrier transport in type-I SL's. 4,5 In weakly coupled, type-I SL's, resonant tunneling in the conduction band usually occurs between different ⌫ subbands. For small carrier densities, the electric-field distribution across the superlattice is homogeneous.…”
mentioning
confidence: 99%